Evaluation of the Knowledge and Attitudes of Dentists Working in a University Hospital in Afyonkarahisar Regarding Rational Drug Use - Ömer Ekici (Selcuk Dental Journal)
Background: This study aims to evaluate the knowledge and attitudes of dentists working in a dental faculty in Türkiye about rational drug use. Methods: In this observational study, a 20-question questionnaire measuring participants' knowledge and attitudes towards rational drug use was administered face-to-face to 59 dentists working in a university hospital in Afyonkarahisar. The obtained data were analyzed with the SPSS-20 program. Results: Fifty-two dentists (16 academics, and 36 research assistants) participated in the study (The participation rate was 89.65%). The most frequently used information sources by the participants while prescribing drugs were the internet (27.56%) and colleagues (24.35%), respectively. Allergic status and pregnancy status were the most frequently asked questions by the participants in the anamnesis of the patients while prescribing drugs (94.2%). approximately one-third (32.7%) of the dentists stated that they did not inform the patient about the "side effects of the drug". The subjects that the participants felt most inadequate about the drugs were price information, bioequivalence, drug interactions and side effects, respectively. 63.5% of the participants think that both the level of medical drug knowledge and the level of knowledge about rational drug use are insufficient. Conclusion: This study revealed the knowledge gaps and the need for training on rational drug use among dentists. to dentists. Rational pharmacotherapy training should be given to dentists before and after graduation. Keywords: Rational drug use; drug prescribing; survey; dentistry; dentist.